2022
DOI: 10.1253/circj.cj-22-0182
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Connections After a Conventional Pulmonary Vein Antrum Isolation in Patients With Atrial Fibrillation

Abstract: wave front propagation, especially in low voltage zones. By performing HDM mapping inside the PVAI lines after conventional encirclement lesions, we hoped to identify any RPs associated with ECs inside our PVAI lines. Thus, the purpose of this study was to determine the prevalence and number of ECs inside the PVAI lines after a conventional PVAI, and the effect of an EC ablation on the outcomes in patients with non-valvular paroxysmal (pAF), persistent (persAF), and long-lasting AF (LLAF). Methods Baseline Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 18 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…Although we could not confirm whether the ECs were conducted from the PVs due to continuation of AF, recent studies have led us to hypothesize that they might have been conducted from the LSPV to the coronary sinus (CS) or Marshall bundle 6 and from the RSPV to the right atrium. 4 , 5 Moreover, we could not confirm the EC directionality. A previous report demonstrated that unidirectional entrance block with SA in the PVs conducted to atrium may prove an incomplete PVAI, while bidirectional block can decrease acute PV reconnections and AF recurrence in patients undergoing PVAI for AF.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although we could not confirm whether the ECs were conducted from the PVs due to continuation of AF, recent studies have led us to hypothesize that they might have been conducted from the LSPV to the coronary sinus (CS) or Marshall bundle 6 and from the RSPV to the right atrium. 4 , 5 Moreover, we could not confirm the EC directionality. A previous report demonstrated that unidirectional entrance block with SA in the PVs conducted to atrium may prove an incomplete PVAI, while bidirectional block can decrease acute PV reconnections and AF recurrence in patients undergoing PVAI for AF.…”
Section: Discussionmentioning
confidence: 71%
“…Due to a suspicion of EC presence, 4–6 all PVs were mapped in detail using EnSite™ with the CMC, and a voltage map was drawn. Isolated RPs were detected at sites 27 and 30 mm distal to the PVAI line at the left superior PV (LSPV) ( Figures 2B and 4A, B ) and right superior PV (RSPV) ( Figures 2C and 4C, D ), respectively.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sinus rhythm still could not be maintained. Because we suspected the presence of ECs, 5 , 6 the LA and PVs were reconstructed in detail by the EnSite system using a steerable high-density mapping catheter (Advisor HD Grid catheter; Abbott, Plymouth, MN) and demonstrated a remaining potential at a 35-mm-distal site from the PVAI line in the left superior pulmonary vein (LSPV; white arrows in Figure 1 D and 1 E). We also confirmed there were no concealed low-voltage signals (CLVSs) 9 along the PVAI lines, indicating the completion of the PVAI lines.…”
Section: Case Reportmentioning
confidence: 99%
“… 1 However, even if using contemporary advanced techniques such as a 3-dimensional mapping system and contact force monitoring, a first-pass isolation is sometimes difficult to perform and additional ablation inside the veins is commonly necessary and effective in achieving these objectives. 4 Recent studies have demonstrated that the presence of epicardial connections (ECs) 5 involving the pulmonary veins (PVs) is one of the mechanisms for failure in achieving a complete PVAI. 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%